Smart and dangerous: How cognitive skills drive the intergenerational transmission of retaliation - Ruby Henry (Institute for the Study of Labor (IZA), 2010)
A need exists to understand how people develop an aggressive, retaliatory conflict resolution policy vs. a more passive reconciliation stance. I contribute a choice-theoretic model that explains how cognitive skills drive the transmission of conflict resolution policies. A child's resolution policy depends on parental effort and the influence of the outside environment. The model has the implication that high-cognitive parents socialize children to their conflict resolution culture more successfully than parents with low cognitive skills. Indeed, I test the model using the cognitive skills and conflict resolution skills of parents and children from the UK National Childhood Development Survey. I find that the parent's effort is reinforced by the prevalence of their conflict resolution values in society. The data confirm that children of retaliating high-cognitive parents are more likely to be socialized to that resolution culture than children of low-cognitive retaliating parents when retaliation is more prominent in society.
Keywords: D10; I20; J13; 330; socioemotional skills; cultural transmission; family influence